2008
DOI: 10.1080/08820530701745231
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Birdshot Chorioretinopathy

Abstract: Birdshot chorioretinopathy is a bilateral, posterior uveitis that affects primarily Caucasians. Although the genetic basis of disease is not completely understood, certain factors are known, such as the strong association with human leukocyte antigen (HLA)-A29. However, given the prevalence of the HLA-A29 allele in the general population, if it were the only factor required for disease, many more people would have birdshot chorioretinopathy. It has been suggested that some environmental factor may trigger this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To date, the association of HLA-A29 with BSCR is the strongest association described between an HLA class I allele and human disease (2,6). Although this association has been known for over three decades (1), lack of understanding of the contribution of HLA-A29 to the pathogenesis of BSCR, impeded it to become an absolute criterion for diagnosis (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the association of HLA-A29 with BSCR is the strongest association described between an HLA class I allele and human disease (2,6). Although this association has been known for over three decades (1), lack of understanding of the contribution of HLA-A29 to the pathogenesis of BSCR, impeded it to become an absolute criterion for diagnosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…BSCR manifests as a severe progressive intraocular inflammation of the posterior eye segment, typically leading to extensive retinal atrophy and blindness (4,5). The disease is most often observed in middle-aged and elderly individuals of European descent and has a slight female predominance (3,6). Current treatment strategies include various immunosuppressive medications but fail to prevent or cease the retinal atrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The role of the differential distribution of HLA-A*29:01 and HLA-A*29:02, the two main subtypes of HLA-A29, in Caucasians and other populations has been actively debated as an explanation for the selective development of the disease in patients of European descent. 14 The respective frequencies of the HLA-A*29:01 and HLA-A*29:02 allele in different populations are summarized in Table 2. It had been suggested that the HLA-A*29:02 subtype is particularly important in conferring risk for birdshot chorioretinopathy.…”
Section: Patient Demographics Hla-a29 Subtypes and Birdshot Choriorementioning
confidence: 99%
“… 10 The HLA-A29 MHC antigen is present in around 7% of Caucasian populations. 11 It is increasingly likely that the association is closer to 100% rather than >95% because false negatives were not so rare when the antibody testing method was used. 12 The rate of false-negative results could be reduced with PCR-based testing.…”
Section: The Importance Of Hla-a29 Histocompatibility Antigen As a DImentioning
confidence: 99%